Simplification Using the Levers of Agility and Devops at Large Financial Organizations - Premchand, Anshu; Sandhya, M.; Sankar, Sharmila (International Journal of Engineering and Technology, 2018)
Most of the huge, conventional organizations we see today are, at a number of levels or the other, finding it difficult to entire in the market, assure their customers and create the software programs the business needs. This is since of the way we introduce and deliver software-there is require of agility with the purpose of business needs, additional constrained by the fact with the purpose of many teams that work for the similar project donâ€™t collaborate in the way needed. Large financial organizations have a completely different set of challenges that need tackling as compared with smaller companies. To solve this problem adoption of agility and DevOps principles for simplification and therefore transformation is more daunting; more so because simplification value needs to be delivered, measured, tracked and make a difference to end customers. This also ensures that some measurable value is delivered every step of the way. But to understand this value, we need to understand the issues that large financial organizations have with the traditional methods of software delivery such as the waterfall approach that have no space for agility and day-to-day business changes or needs. Agility and DevOps are response to many of these challenges in approaches such as waterfall method for software delivery in a large financial enterprise. This study presents a stark and welcome change from waterfall methodology where there will be very few examples of delivery within projected cost, time and effort. This plan will lead to micro-plans to manage each of the planned stages of agile transformation of the architecture space for the organization. It also focuses on simplification of complex technological world at large organizations and role of agility and DevOps therein to deliver maximum business & customer related results.Â